Management of Tourism Object Policy in Sumedang Regency Culture - Imam Maulana, Muhammad; Nugraha, Denis (Decision, 2025)
This study has a background regarding employee competency for managing tourism destinations in the tourism and cultural service sector of Sumedang Regency. The author is interested in researching this problem because he wants to know more about Employee Competency for Managing Tourism Destinations in the Tourism and Cultural Service Sector of Sumedang Regency. Based on the results of observations in the field, there are several problems, namely regarding Knowledge, Understanding, Ability/Skills, Values, Attitudes and Interests. The theory used in this study is the theory according to Gordon in Sutrisno (2011:204). The objectives of this study are 1) To determine employee competency for managing tourism destinations in the tourism and cultural service sector of Sumedang Regency. 2) To determine the dimensions analyzed regarding employee competency for managing tourism destinations in the tourism and cultural service sector of Sumedang Regency. With this research, the author uses a qualitative approach method and a descriptive method, data collection techniques using interview techniques, which are conducted to the Head of the General and Personnel Sub-Division, Head of the Sub-Destination UPT Sumedang Region and the Sub-General and Personnel Apparatus of the Pangandaran Regency Tourism and Culture Office, observation and documentation. The data obtained in this study were processed using qualitative procedures according to Miles & Huberman (1992:16) including data reduction analysis techniques, data presentation, and conclusion drawing. The conclusion of this study is that employee competence for managing tourism destinations is still not fully running well and is still less than optimal in its management because of the lack of employee resources and the lack of use of information technology in managing tourism objects. The researcher's suggestion for the Sumedang Regency Tourism and Culture Office in managing tourism destinations in Sumedang Regency must be more active and develop further in improving employee competency in managing tourism destinations so that in terms of improvements related to tourism objects, it can run well and be more advanced in the management carried out by the office employees to be able to improve various management promotions that use media, the internet and social media in processes related to employee competency for managing tourism destinations in Sumedang Regency.